Solid pseudopapillary epithelial neoplasia of the pancreas causing sinistral portal hypertension: a case report - Mishra, Akshat; Bakhshi, Girish D.; Yadav, Rajesh; Doddamalappa, Samprati; Chanap, Mahesh; Sholapur, Sachin; Malgaonkar, Sumit; Suradkar, Kunal (International Surgery Journal, 2021)
Solid pseudopapillary epithelial neoplasm (SPEN), also referred as Franz’s tumour or Hamoudi’s tumour is a low malignant potential epithelial neoplasm of the pancreas. It occurs at a much lower frequency than other cystic neoplasms of the pancreas. It occurs rarely and in young females. Although infrequently, large sized tumours are known to compress the splenic vein thereby resulting in extra hepatic portal venous obstruction (EHPVO) resulting in left sided portal hypertension (PHT). The resulting periportal collateral circulation poses an intraoperative challenge while approaching these tumors. Meticulous pre-operative planning can go a long way in managing such a case and providing complete surgical cure. We present a case of SPEN in a 37 years old female which was discovered incidentally and managed surgically to achieve a complete cure to both the tumour and the left sided PHT.